Juridical Review of the Impact of Law Enforcement on Environmental Damage and Sustainable Development in Jurisdiction in Medan City - Mulyanda, Intan; Simanjuntak, Sahala D; Nazara, Berkat Firman Jaya; Berutu, Sigar P. (IHSA Institute, 2024)
Juridical review of the impact of law enforcement on environmental damage and sustainable development in the jurisdiction of Medan city. The focus of the research raised is: 1) What is the impact of law enforcement of environmental damage on sustainable development in the city of Medan; How effective is the implementation of policies related to law enforcement against environmental damage in the city of Medan. Empirical normative methods were used in this study. In other words, this study uses empirical normative legal cases that are products of legal behavior, such as evaluating the implementation of credit agreements. The results of this study are: Knowing the impact of law enforcement of environmental damage on sustainable development in the city of Medan, knowing the effectiveness of policy implementation related to law enforcement against environmental damage in the city of Medan